Application of MIKE model for simulation of wastewater dispersion in the project of eco-tourism and residential areas of Rach Tram - Phu Quoc, Kien Giang, Vietnam - Vu , Van Lan; Nguyen, Hong Lan; Bui, Dac Thuyet; Ngo, Tra Mai (Vietnam Journal of Marine Science and Technology, 2023)
This study aims to explore the transmission of pollutants from the domestic wastewater of the Rach Tram - Phu Quoc eco-urban project. To achieve this, the Ecolab module of the Mike model is employed. The dispersion of pollutants is influenced by both hydraulic and wind conditions. Notably, under southwest wind condition, the dispersion of pollutants is considerably more pronounced compared to that observed during the Northeast monsoon. Pollutant concentrations exhibited a tendency to move upstream along the Rach Tram river during high tide, while during low tide periods, they tended to move towards the sea. The results of the study indicated that concentrations of Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD5), Ammonium (NH4+), and Total Phosphorus (TP) in the Rach Tram River and its estuary were found to be 3–8 times higher than the defined standard of Vietnam. However, when appropriate wastewater treatment measures were implemented (scenario 2), the levels of pollutants were observed to be lower the permissible environmental protection standards.